2019
DOI: 10.1371/journal.pmed.1002910
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phospholipid n-3 and n-6 polyunsaturated fatty acids in relation to cardiometabolic markers and gestational diabetes: A longitudinal study within the prospective NICHD Fetal Growth Studies

Abstract: BackgroundDespite dietary recommendations of polyunsaturated fatty acids (PUFAs) for cardiometabolic health, n-3 and n-6 PUFAs and their interplay in relation to diabetes risk remain debated. Importantly, data among pregnant women are scarce. We investigated individual plasma phospholipid n-3 and n-6 PUFAs in early to midpregnancy in relation to subsequent risk of gestational diabetes mellitus (GDM).Methods and findingsWithin the National Institute of Child Health and Human Development (NICHD) Fetal Growth Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 59 publications
3
71
2
Order By: Relevance
“…The similarity in longitudinal profiles between eicosanoids and fatty acids is expected, as fatty acid metabolism directly influences eicosanoid production [ 12 ]. Our observations are consistent with epidemiologic evidence of changes in fatty acid levels across pregnancy [ 31 34 ]. However, this comparison must be interpreted cautiously, as these prior studies primarily quantified esterified or total fatty acids and we measured free fatty acid levels.…”
Section: Discussionsupporting
confidence: 90%
“…The similarity in longitudinal profiles between eicosanoids and fatty acids is expected, as fatty acid metabolism directly influences eicosanoid production [ 12 ]. Our observations are consistent with epidemiologic evidence of changes in fatty acid levels across pregnancy [ 31 34 ]. However, this comparison must be interpreted cautiously, as these prior studies primarily quantified esterified or total fatty acids and we measured free fatty acid levels.…”
Section: Discussionsupporting
confidence: 90%
“…Although these metabolite differences were not statistically significant in single metabolite analyses, this metabolic profile was significantly different during early versus mid-pregnancy. In previous studies, some of these metabolites have been linked to insulin resistance, pregnancy, or both [23][24][25][26][27][28][29][30][31]. Previous studies have observed relative decreases in fatty acids post-OGTT among pregnant women [19,20], but this is the first study to measure metabolites during both early and mid-pregnancy.…”
Section: Changes In Metabolites During An Ogtt At Early Versus Mid-prmentioning
confidence: 87%
“…Studies suggest that acyl carnitines are tightly regulated, decrease in women during pregnancy [26,27], and have been associated with maternal and child overweight and obesity [28]. Docosapentaenoate (DPA), a fatty acid, has been inversely correlated with insulin resistance markers, and circulating levels tend to decrease during pregnancy [29]. Bile acids are tightly regulated during pregnancy and increases are indicative of intrahepatic cholestasis of pregnancy [30,31].…”
Section: Changes In Metabolites During An Ogtt At Early Versus Mid-prmentioning
confidence: 99%
“…It is reported that D6D, elongase and D5D play a key role in the metabolic pathway of LA ( 29 ). Abundant evidences containing animal experiment ( 30 ), cross-sectional research ( 23 ) and cohort study ( 24 ) reveal that abnormal PUFAs metabolism in diabetic patients is closely related to the activities of desaturation and elongase depending on the comparison between diabetic patients and their counterparts. In the current study, the association between the levels of PUFAs and the presence of DR do not achieve significant level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activities of desaturase and elongase are closely linked to the metabolism of n-6 PUFAs, so we have also explored the activities of desaturase and elongase, in which these activities are estimated from the product-to-precursor ratios of some individual fatty acids in serum ( 23 ). The 18:3 n-6/18:2 n-6 (GLA/LA), 20:4 n-6/20:3 n-6 (AA/DGLA) and 20:3 n-6/18:3 n-6 (DGLA/GLA) are commonly suggested to represent the activities of D6D, delta 5-desaturase (D5D) and elongase, respectively ( 24 ).…”
Section: Design and Methodsmentioning
confidence: 99%